A Web-Based General Service Provider - Ali, Jauhar (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we report about the design and implementation of a web-based prototype system for allowing consumers to access general services using their computers or handheld devices. The aim of the work is to use technology to assist people having a daily routine of work in getting needed services that may hinder their regular work. These services include housekeeping, vehicle maintenance, child tutoring, and many others. We proposed and developed a web-based general service provider system where business entities can offer their services and consumers can book and use those services. Such a system can greatly save consumers' time and lower their stress level as they will be relieved to focus on their daily routine work.